Outcomes following Structural Grafting of Distal Femoral Osteochondral Injuries in Patients Aged 40 Years and Older - Degen, Ryan M.; Coleman, Nathan W.; Chang, Brenda; Tetreault, Danielle; Mahony, Gregory T.; Williams, Riley J. (The Journal of Knee Surgery, 2017)
Osteochondral lesions of the distal femur represent a challenging clinical entity, particularly in patients > 40 years of age. Microfracture has demonstrated inferior results in this population with clinical deterioration beyond 1 to 2 years postoperatively. Limited evidence exists to support alternative cartilage restoration procedures. The purpose of this study was to report functional outcomes and activity levels following cartilage restoration procedures in patients > 40 years with symptomatic distal femoral osteochondral lesions. From 2000 to 2012, 61 patients with distal femoral osteochondral injuries were retrospectively identified. Mean follow-up was 3.6 ± 1.4 years; mean age was 51.6 years (range 40–71); 59% were male. Of 61 patients, 35 patients (57%) were treated with synthetic scaffold (SS) plugs (off-label), 14 (23%) with osteochondral allograft (OCA), and 12 (20%) with autologous osteochondral transfer (AOT). Validated outcome measures including activity of daily living (ADL) score, International Knee Documentation Committee (IKDC) subjective evaluation form, and Marx activity scale (MAS) were used. The average lesion size was 3.8 ± 2.1 cm2. Lesion size was significantly greater in the OCA group (5.8 ± 1.8 cm2), compared with the SS (3.2 ± 1.9 cm2) and AOT group (3.3 ± 1.8 cm2, p ≤ 0.0024). Collectively, outcome scores for the entire population demonstrated significant improvement in ADL (61.36 ± 17.76–76.81 ± 17.2, p < 0.0001) and IKDC scores (40.28 ± 13.28–61.84 ± 20.83, p < 0.001) from baseline to final follow-up, with no significant change in MAS (4.19 ± 5.13–2.59 ± 3.92, p = 0.07). Similarly, subgroup analysis identified that all treatment groups (SS, OCA, and AOT) demonstrated significant improvement in ADL and IKDC scores from preoperative to final postoperative visit (p ≤ 0.0361). MAS scores were maintained in the OCA and AOT groups (p ≥ 0.1704), but significantly decreased in the SS group (4.3 ± 5.2–2.7 ± 4.11, p = 0.0163). Ten patients (16.3%) required revision surgery at a mean of 4.4 years (range 0.3–13.4 years). Cartilage restoration procedures using structural grafts are successful in patients 40 years and older, with improved pain and functional outcome scores compared with preoperative baseline scores. OCA and AOT should primarily be used, given recent concerns with SS implants.
Keywords: knee; cartilage restoration; articular cartilage; osteochondral defect